Peranan Bidang Pariwisata di Disparpora Kabupaten Pelalawan dalam Pengembangan Kawasan Objek Wisata Bono - Andry, Hendry; Gesmi, Irwan (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This research aimed to determine the role of Tourism and Sports Department of Pelalawan Regency (specially tourism sector) in developing Bono as tourist attraction. This descriptive analytical research used both primary and secondary data sources with observation as data collection technique. The result showed the role of Tourism and Sports Department of Pelalawan Regency (specially tourism sector) in developing Bono has been implemented optimally. Out of four indicators (Regulator, Dynamist, Facilitators and Catalysts), Regulator as the only indicator has been fully implemented. Meanwhile on Facilitator, it has been implemented, however there has many obstacles, such as lack of facilities and infrastructure. Thus, this indicator is only carried out under certain conditions. Furthermore, Kampung Bono and Pantai Ogis are given less attention and underused in creating the well-being of the local community, local and foreign tourists.